Antimicrobial potential of a hydrolyzed protein extract of the microalgae Nannochloropsis sp. (2019)
ABSTRACT : Microalgae are photosynthetic microorganisms widely used at the industrial level because of their high content of compounds with bioactive properties such as antimicrobial peptides. These compounds have a wide range of action mechanisms, do not produce the resistance of conventional antibiotics and could be effective against bacteria, fungi, viruses, parasites, and even tumor cells. In this work, by mechanical cell lysis treatment, a protein extract of dry biomass of Nannochloropsis sp was obtained, subsequently, it was hydrolyzed with an enzyme complex of proteases, papain, and pancreatin, for 6 hours, at 44 ° C and pH 7. Finally, the antimicrobial activity of the fraction of hydrolyzed extract with a size less than 3 kDa was evaluated against Staphylococcus aureus, Escherichia coli, and Candida albicans, obtaining a percentage of growth inhibition of 93.1%, 96.6%, and 14.4% respectively, which represents a peptic extract with bacteriostatic and fungistatic properties.